KEWENANGAN CAMAT DALAM MENGOORDINASIKAN PENERAPAN DAN PENEGAKAN PERATURAN DAERAH NOMOR 10 TENTANG SUMBER DAYA AIR DAN SUMUR RESAPAN DI KECAMATAN TAMPAN TAHUN 2012 - Sabana, Lindra; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study was conducted to describe how the authority of head of the district in coordinating the implementation and enforcement of Regional Regulations No. 10 of 2006 on Water Resources and Infiltration wells in Tampan District in 2012. Not optimal implementation and enforcement of regional regulations on water resources and infiltration wells in Tampan District result in flooding. With the problems that arise in the implementation and enforcement this regulation in the Tampan District, head of the district which has the authority should to coordinate the implementation and enforcement of legislation which have been regulated in Government Regulation No. 19 Year 2008 on the District to coordinate the implementation and enforcement of regulations related areas of water resources and infiltration wells with working units authorized, the Planning Office space and Buildings Pekanbaru and Civil Service Police Unit Pekanbaru city.This research is a descriptive study using a qualitative approach as a tool of analysis. This research was conducted in the Tampan District, Pekanbaru. This research uses documentation (observation) and interviews with key informants as information objects that aim to achieve the goal to get the information in the study. Data used in this study is primary data and secondary data obtained through direct observation and interviews with key informants in this study.Head of district authority is in effectiveness in coordinating the implementation and enforcement of Regional Regulations No. 10 of 2006 on Water Resources and Infiltration wells due regard Head of Tampan District coordination in the implementation and enforcement of regional regulations is not Head of district Tampan authority to exercise it . This is due to the lack of delegation of authority related to the coordination of Pekanbaru Mayor implementation and enforcement of local regulations on water resources and recharge wells . As for the factors that hinder the implementation of the sub-district head authority in coordinating the implementation and enforcement of Regional Regulations No. 10 of 2006 includes (a) Internal factors , among others, (1) Understanding head of district the attributive authority in coordinating the implementation and enforcement of legislation. (2) Leadership the head of district is unresponsive. (3) The complexity of the problem being addressed by head of ditrict untill less optimal handling on an issue. (b) External Factors absence of official communication and building layout to coordinate any events or problems that occur with regard to the implementation of regional regulations on water resources and infiltration wells with head of Tampan Distirct officials and Leaders of the Police Force Pekanbaru.Keywords : Authority , Coordination , Regional Regulation.